PENGARUH INCOME LEVEL IN MUNICIPALITY, GENERAL ALLOCATION FUND, NUMBER OF LOCAL PARLIAMENTS DAN HUMAN DEVELOPMENT INDEX TERHADAP TINGKAT PENGUNGKAPAN LAPORAN KEUANGAN PEMERINTAH DAERAH - Afifah Muawanah (2022)
This study aims to examine the effect of income level in municipality, general allocation fund, number of local parliaments, and human development index on the level of disclosure in local government financial statements. The population of this study is all regional government's financial report in Indonesia. The sample on this study consisted of 455 The District / City Governments on Sumatera Island in 2017- 2019. Hypothesis testing in this study used Multiple Linier Regression Analysis with STATA version 16. Based on the result of data analysis, it can be concluded that income level in municipality and general allocation fund have no effect on the level of disclosure in local government financial statements. Meanwhile, number of local parliaments and human development index have a positive and significant effect on the level of disclosure in local government financial statements.